2017
DOI: 10.1007/978-3-319-68557-1_12
|View full text |Cite
|
Sign up to set email alerts
|

Smart City Participation: Dream or Reality? A Comparison of Participatory Strategies from Hamburg, Berlin & Enschede

Abstract: Urbanization is forcing local government to revisit their way of communicating with citizens. By using Information Technology, cities can become smarter, more livable and more sustainable. The purpose of this study is to identify critical success factors for local government regarding smart city strategy and participation. The literature study consists of concepts such as smart city, participation and digital strategy. The qualitative study shows that the city of Hamburg defined a digital vision while the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
(60 reference statements)
0
7
0
1
Order By: Relevance
“…We also evaluated each item on the integrated dashboard on a scale from 1 to 6 (two items were eliminated due to unavailability of relevant information on some cities analyzed-citizen-government channels and public services for people with limited mobility-ultimately leaving 40 items). The data are obtained from different public sources available to citizens, such as the various cities' City Councils, open data published by the Spanish government, the official webpages of regional governments, local newspapers, and the Andalusian Multiterritorial Information System (SIMA) [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. If the city is successful in each field (for example, obtains a 6 in all fields), it can obtain a maximum of 240 points.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also evaluated each item on the integrated dashboard on a scale from 1 to 6 (two items were eliminated due to unavailability of relevant information on some cities analyzed-citizen-government channels and public services for people with limited mobility-ultimately leaving 40 items). The data are obtained from different public sources available to citizens, such as the various cities' City Councils, open data published by the Spanish government, the official webpages of regional governments, local newspapers, and the Andalusian Multiterritorial Information System (SIMA) [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. If the city is successful in each field (for example, obtains a 6 in all fields), it can obtain a maximum of 240 points.…”
Section: Discussionmentioning
confidence: 99%
“…Other cities, such as Hamburg and Bergen [58,59], have developed projects to remedy the deficiencies detected: projects which are currently global models of urban efficiency. In the case of Spain, a study by the University of Navarre [59] showed the world ranking of various Spanish cities (Figure 5.)…”
Section: Proposed Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In einer passiven Rolle kann zudem Citizen Sensing genutzt werden, um auf Grundlage der so erhobenen Daten politische Entscheidungen, zum Beispiel im Straßenbau zur Verbesserung der Verkehrsführung, zu treffen. BürgerInnen dienen in vielen Fällen primär als Informationsquelle, beispielsweise für Smartphone-Umfragen der Stadt Hamburg (Spil et al 2017) (Hosio et al 2014).…”
Section: Politische Beteiligung Von Smart Citizensunclassified
“…The rise of Web 2.0 and social media through the last years has significantly transformed the way people communicate with each other (Münster et al., 2017; Spil et al., 2017; Grenier and Kudo, 2016; Stratigea, 2015; Kubicek, 2010). This change concerns mainly the supplementary function of communication through new technologies and, in contrast with what utopians and distopians say, is not characterized solely from positive or negative impacts, respectively (Wellman et al., 2001) (Wellman et al., 2001).…”
Section: Theorymentioning
confidence: 99%